Cultivating Critical Translingual Awareness: Challenges and Possibilities for Teachers and Teacher Educators. (August 2022) - Cinaglia, Carlo; De Costa, Peter I
Translanguaging has been put forth as an asset-based perspective to language education that recognizes the diverse communicative repertoires of plurilingual students. In this thematic review, we highlight the potential of translanguaging as a pedagogical approach in fostering educational equity and generating critical dialogue among various stakeholders. We draw attention to recent theorization of translanguaging within a broader decolonial agenda, and we highlight challenges faced implementing translanguaging pedagogies in different contexts. Finally, we underscore the role of teacher educators in helping teachers develop a critical translingual stance focused on interrogating dominant ideologies about language and education.